Topical hemostatic powder promotes reepithelialization and reduces scar formation after extensive esophageal mucosal resection. Issue 6 (1st September 2016) - Beye, B.; Barret, M.; Alatawi, A.; Beuvon, F.; Nicco, C.; Pratico, C. A.; Chereau, C.; Chaussade, S.; Batteux, F.; Prat, F.
Summary: The development of techniques for endoscopic resection has provided new strategies for radical conservative treatment of superficial esophageal neoplasms, even those that are circumferential, such as Barrett's neoplasia. However, it is necessary to prevent the formation of scar tissue that can be responsible for esophageal strictures following circumferential resection. Preliminary data have suggested the possible efficacy of a hemostatic powder in the promotion of wound healing. The study aims to assess the effectiveness of Hemospray (Cook Medical) in a swine model of post-endoscopic esophageal stricture. Our prospective controlled study included 21 pigs. A 6-cm circumferential submucosal dissection of the esophagus (CESD) was performed in each pig. Group 1 ( n = 11) only underwent CESD and Group 2 ( n = 10) had repeated Hemospray applications after CESD. Clinical, endoscopic, and radiological monitoring were performed, blood levels of four inflammatory or pro-fibrotic cytokines were assessed, and histological analysis was performed. Median esophageal diameter was greater in the group treated with Hemospray (2 mm [1–3] vs. 3 mm [2–4], P = 0.01), and the rate of symptomatic esophageal stricture was 100% and 60% in Groups 1 and 2, respectively ( P = 0.09). The thicknesses of esophageal fibrosis and inflammatory cell infiltrate were significantly lower in Group 2 than in Group 1 ( P = 0.002 and 0.0003, respectively). The length of the neoepithelium was greater in Group 2 than in Group 1 ( P = 0.0004). Transforming growth factor-β levels were significantly lower in Group 2 than in Group 1 ( P = 0.01). The application of Hemospray after esophageal CESD reduces scar tissue formation and promotes reepithelialization, and therefore is a promising therapeutic approach in the prevention of post-endoscopic esophageal stricture.